2016
DOI: 10.1155/2016/9074062
|View full text |Cite
|
Sign up to set email alerts
|

The Identification and Synthesis of Lead Apatite Minerals Formed in Lead Water Pipes

Abstract: Phosphate is added to drinking water in the UK to minimise the release of lead from lead water pipes. The phosphate encourages the formation of insoluble lead apatites on the walls of the pipe. Hydroxylpyromorphite Pb5(PO4)3OH is the lead apatite that is most often used to model lead levels in tap water; however, its presence has not been confirmed. Our aims were to identify the lead pipe apatite and synthesise it. The synthetic mineral would then be used in future solubility studies to produce better predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 40 publications
3
45
0
Order By: Relevance
“…Peters et al 34 , using spectrometric techniques to study lead service drinking water pipes, showed that lead carbonates were formed under pH adjusted-waters, and species like apatite were observed when orthophosphoric acid was added. This is in agreement with Hopwood et al 35 , who found that lead water pipes from Yorkshire (UK), fed with PO 4 3− treated drinking water, contained a variety of apatite minerals, included lead apatite species which are the least soluble form of lead 36 . In addition, microorganisms have the potential to induce metal precipitation in a range of environmental settings.…”
Section: Discussionsupporting
confidence: 92%
“…Peters et al 34 , using spectrometric techniques to study lead service drinking water pipes, showed that lead carbonates were formed under pH adjusted-waters, and species like apatite were observed when orthophosphoric acid was added. This is in agreement with Hopwood et al 35 , who found that lead water pipes from Yorkshire (UK), fed with PO 4 3− treated drinking water, contained a variety of apatite minerals, included lead apatite species which are the least soluble form of lead 36 . In addition, microorganisms have the potential to induce metal precipitation in a range of environmental settings.…”
Section: Discussionsupporting
confidence: 92%
“…However, there are many uncertainties and potential errors in the simulations resulting from the absence or choice of equilibrium constants, variations in the physical solubility due to different solid phase purity and crystallinity, temperature-dependent variations of the equilibrium constants, and unknown rates of precipitation versus dissolution reactions (Edwards, Jacobs, & Dodrill, 1999;Noel, Wang, & Giammar, 2014;Schock & Sandvig, 2004). For example, studies have not conclusively determined the factors causing the specific formation of observed Pb(II) orthophosphate solids such as Pb 5 (PO 4 ) 3 OH (hydroxypyromorphite), Pb 5 (PO 4 ) 3 Cl (pyromorphite), or tertiary lead phosphates (Pb 3 (PO 4 ) 2 , Pb 9 (PO 4 ) 6 ) (Hopwood et al, 2016). Furthermore, studies Hayes, Croft, Phillips, Craik, & Schock, 2016;Kim & Herrera, 2010;Schock, Cantor, Triantafyllidou, Desantis, & Scheckel, 2014;Snoeyink et al, 2003;Wasserstrom, Miller, Triantafyllidou, Desantis, & Schock, 2017) have noted the extensive presence of amorphous solid phases in a number of drinking water distribution systems (DWDSs).…”
Section: Introductionmentioning
confidence: 99%
“…The EU recognizes Pb as one of the substances known to cause direct health impacts, and as a result has proposed to lower the drinking water limit to 5 µg/L [5]. However, a number of reports from both the EU [6] and regions outside, such as the USA [7], Australia [8] and Pakistan, [9] have highlighted Pb drinking water levels that exceed this level.…”
Section: Introductionmentioning
confidence: 99%